Internal audit effectiveness in the Malaysian local authorities: internal auditors’ perspectives / Halimah @ Nasibah Ahmad - Ahmad, Halimah @ Nasibah (Institute of Graduate Studies, UiTM, 2014)
Similar to other public sector organizations, local authorities are facing increasing demand for governance and accountability. Hence, it was strongly recommended by various parties that it is necessary for all local authorities to have an effective internal audit function. Internal audit provides assistance to an organization in achieving its objectives through assessing and improving the effectiveness of risk management, control and governance processes. The main objective of this study is to investigate the influence of the internal and external organizational factors on the internal audit effectiveness in the Malaysian local authorities.